Searching for the sound : my life with the Grateful Dead - Lesh, Phil, 1940- (New York : Little, Brown, 2005)
The bass player for arguably the greatest improvisational band in American history tells the story of his life, Jerry Garcia, and the Grateful Dead.
Keywords: Lesh, Phil, -- 1940-; Grateful Dead (Musical group); Bass guitarists -- United States -- Biography; Rock musicians -- United States -- Biography